Availability, Use and Constraints to Use of Electronic Information Resources by Postgraduates Students at the University of Ibadan - Adeleke, Dare Samuel; Ngozi Nwalo, Kenneth Ivo (International Journal of Knowledge Content Development & Technology, 2017)
Availability, awareness and use of electronic resources provide access to authoritative, reliable, accurate and timely access to information. The use of electronic information resources (EIRs) can enable innovation in teaching and increase timeliness in research of postgraduate students which will eventual result into encouragement of the expected research-led enquiry in this digital age. The study adopted a descriptive survey design. Samples of 300 of postgraduate students within seven out 13 Faculties were randomly selected. Data were collected using questionnaire designed to elicit response from respondents and data were analyzed using descriptive statistics methods percentages, mean, and standard deviation. Results indicated that internet was ranked most available and used in the university. Low level of usage of electronic resources, in particular, full texts data bases is linked to a number of constraints: Interrupted power supply was ranked highest among other factors as speed and capacity of computers, retrieval of records with high recall and low precision, retrieving records relevant to information need, lack of knowledge of search techniques to retrieve information effectively, non possession of requisite IT skills and problems accessing the internet. The study recommended that usage of electronic resources be made compulsory, intensifying awareness campaigns concerning the availability, training on use of electronic resources and the problem of power outage be addressed. URL: http://ijkcdt.net/xml/12712/12712.pdf